The morphology, sedimentology and palaeoenvironmental significance of two pan-lunette clusters in the Southwestern Cape of South Africa - Gaines, Sarah Margaret (University of Cape Town, 2014)
Bibliography: leaves 95-107. === Two clusters of pans and associated lunette dunes are distinct landscape featurs in the Swartland and Agulhas Plain regions of the southwestern Cape of South Africa. While occurring in geographic proximity within the Winter Rainfall Region, each of the pan-lunette clusters is hosted by different substrates, subjected to different coastal climate regimes and exhibits different morphology, orientation of features, and sedimentological characteristics. Not only are geomorphic characteristics at variance between regions, but also the alignment of lunettes on the leeside of pans, parallel within the cluster, is at variance with predominant modern wind direction and seasonality of precipitation at both sites, although the difference is more pronounced at Agulhas. In order to elucidate the occurrence and formational processes of these features, a dual-scale approach was employed: a regional cartographic study coupled with detailed local sedimentological analyses. The geomorphic characteristics of these features were quantified using aerial photography and orthophotographic maps. Dry season palaeo-wind direction was inferred from the regional analysis; in Agulhas, winds must have been blowing from WSW during the dry season, similar to modern wet season winds.